2017
DOI: 10.1242/jcs.194662
|View full text |Cite
|
Sign up to set email alerts
|

GSK3-mediated CLASP2 phosphorylation modulates kinetochore dynamics

Abstract: Error-free chromosome segregation requires dynamic control of microtubule attachment to kinetochores, but how kinetochoremicrotubule interactions are spatially and temporally controlled during mitosis remains incompletely understood. In addition to the NDC80 microtubule-binding complex, other proteins with demonstrated microtubule-binding activities localize to kinetochores. One such protein is the cytoplasmic linker-associated protein 2 (CLASP2). Here, we show that global GSK3-mediated phosphorylation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…While the curved conformation of polymerizing and depolymerizing KT-attached MT plus-ends could not be distinguished at the ultrastructural level (McIntosh et al, 2008;McIntosh et al, 2018;McIntosh et al, 2013), our study indicates that CLASPs might be able to recognize these two functional states through interaction with EB-proteins that specifically track growing MT plus-ends and were recently shown to distinguish their structural state (Reid et al, 2019). Interestingly, although not fully abolished, CLASP2 association with EB1 at growing MT plus-ends is negatively regulated by CDK1-and GSK3β-mediated phosphorylation close to the CLASP2 SxIP motifs during mitosis (Kumar et al, 2012;Kumar et al, 2009;Wittmann and Waterman-Storer, 2005), and this fine regulation might be important for chromosome segregation fidelity (Pemble et al, 2017). Indeed, our findings revealed that mutation of the CLASP2 SxIP motifs was sufficient to compromise efficient error correction, giving rise to chromosome segregation errors.…”
Section: Discussionmentioning
confidence: 72%
“…While the curved conformation of polymerizing and depolymerizing KT-attached MT plus-ends could not be distinguished at the ultrastructural level (McIntosh et al, 2008;McIntosh et al, 2018;McIntosh et al, 2013), our study indicates that CLASPs might be able to recognize these two functional states through interaction with EB-proteins that specifically track growing MT plus-ends and were recently shown to distinguish their structural state (Reid et al, 2019). Interestingly, although not fully abolished, CLASP2 association with EB1 at growing MT plus-ends is negatively regulated by CDK1-and GSK3β-mediated phosphorylation close to the CLASP2 SxIP motifs during mitosis (Kumar et al, 2012;Kumar et al, 2009;Wittmann and Waterman-Storer, 2005), and this fine regulation might be important for chromosome segregation fidelity (Pemble et al, 2017). Indeed, our findings revealed that mutation of the CLASP2 SxIP motifs was sufficient to compromise efficient error correction, giving rise to chromosome segregation errors.…”
Section: Discussionmentioning
confidence: 72%
“…The FUCCI plasmids pCDII-EF-MCS containing mKO2-hCdt1(30/120) and mAG-hGeminin(1/110) have been described previously (Sakaue-Sawano et al, 2008) (GenBank accession number AB370332 and AB370333). H2B-mCherry pLenti6/V5-DEST has been described previously (Pemble et al, 2017). For inducible shRNA expression, the following short hairpin sequences were cloned into the Tet-PLKO-puro vector as published (Wiederschain et al, 2009): shTPX2 no.…”
Section: Methods Details Lentiviral Constructs and Cloningmentioning
confidence: 99%
“…Subsequently, to generate cell lines stably expressing GFP-tubulin, inducible NuMA and dynein knockout cells were infected with GFP-tubulin lentivirus and selected with 2.5 mg/mL blasticidin. Virus was made in HEK293T cells from a pLenti6/V5-DEST plasmid (Invitrogen) containing GFP-tubulin (gift of T. Wittmann [49]). Four days before each experiment, spCas9 expression was induced with 1 mM doxycycline hyclate.…”
Section: Experimental Model and Subject Detailsmentioning
confidence: 99%